The Role of Pharmacist in the Health Care System: Current Scenario in India - Saurabh Nimesh (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Pharmacists are society's specialists on drugs. The Pharmacist of today is a drug-maker, drug-dispenser, drug-custodian, patient-counselor, drug-researcher, and drug-educator and above all an honest and patriotic citizen. The techno-proficient foundation of the drug expert gives him/her the certainty of providing services with a moral way to deal with the satisfaction of patients. The consecrated qualities are required to be cherished and professed by the pharmacist. Pharmacists assume a significant job in giving health care services, benefits by means of community pharmacy services in rural areas where physicians are not accessible or where physician services are unreasonably expensive for meeting the health care necessities. The paper at that point recognizes how pharmacists give expanded services, identifies key challenges and barriers, and suggests rules and regulations that could help secure open doors for pharmacists to play out an extended job.